ANALISIS EMPIRIK PENGGUNAAN INTERNET BANKING DAN MOBILE PHONE BANKING PADA BANK SYARIAH DI MASA PANDEMI COVID-19 (STUDI DI KECAMATAN DRAMAGA, KABUPATEN BOGOR). - Oktavia, Tasya Audina; Trihantana, Rully; Anwar, Miftakhul (SAHID BANKING JOURNAL, 2023)
During this pandemic covid-19, we are required to keep our distance and it is recommended to stay at home, this makes all Islamic banks provide internet-based services to make it easier for customers to make transactions. the importance of using internet-based services such as internet banking and mobile phone banking during the pandemic was felt directly by customers in Dramaga District, this made it easier for researchers to analyze empirically the use of internet banking and mobile phone banking at Islamic banks during the pandemic covid-19. The study used a descriptive qualitative method with a phenomenological approach to research subjects in the Dramaga sub-dist rict. The results of this study indicate that the habit and use of internet banking and mobile phone banking is very high, because customers in Dramaga District feel safe and cost-effective in internet-based use, in addition to being very easy to use, internet banking and mobile phone banking can also be used anytime and anywhere. anywhere. can be seen from the high statement of the factor analysis used. The use of internet-based transactions for the community in Dramaga District must be developed again because its use is very efficient, time-saving and can be used 24 hour.